Pengaruh Kombinasi Pupuk Hayati Konsorsium cair dengan Pupuk N, P, K terhadap Populasi Azotobacter sp., Serapan N, Bobot Kering dan Hasil Selada (Lactuca sativa L.) pada Andisols Lembang - Setiawati, Mieke Rochimi; Lubis, Ary Satria; Sudirja, Rija; Suryatma, Pujawati; Setiawan, Ade; Herdiyantoro, Diyan (Soilrens, 2024)
Andisols area is potentially developed as horticulture cultivation area such as lettuce. The low number of productions of lettuce in Indonesia can be optimized by fertilization. The application of biofertilizer is expected to intensify the efficiency of inorganic fertilization through the ability of nitrogen fixation bacteria. The aim of study was evaluating the effect of a combination between liquid biofertilizer consortium with N, P, K fertilizer on N-uptake, population of Azotobacter sp., dry biomass, and yield of lettuce (Lactuca sativa L.) in Andisols. This study was done in June 2015 until September 2015 in 2 locations, Balai Besar Pelatihan Pertanian in Kayuambon, Lembang, West Java with an altitude of 2084 meters above sea level and in Soil Biology Laboratory, Soil Science Department, Universitas Padjadjaran. As treatment, seven combination dose of fertilizer A = control (without any fertilizer); B = 100% dosage recommendation of N, P, K; C = liquid biofertilizer consortium 10 L ha-1; D = liquid biofertilizer consortium 10 L ha-1 + 100% dosage recommendation of N, P, K; E = liquid biofertilizer consortium 10 L ha-1 + 75% dosage recommendation of N, P, K; F = liquid biofertilizer consortium 10 L ha-1 + 50% dosage of recommendation of N, P, K; G = liquid consortium biofertilizer 10 L ha-1 + 25% dosage recommendation of N, P, K). The research design was in the complete Randomized Block Design (RBD) with four replications. Regarding the yield performance and population of Azotobacter sp. which is better than the other treatments is a treatment with liquid biofertilizer consortium 10 L ha-1 + 50% dosage of recommendation of N, P, K. The significant positive correlation between the yeild of lettuce with dry mass is 96.8% and nitrogen uptake of 84.2%